Optimal Kernel Parameters of Smooth-Windowed Wigner-Ville Distribution for Power Quality Analysis - Abdullah, Abdul Rahim; ahmad, Nur Hafizatul Tul Huda; Sha'ameri, Ahmad Zuri; abidullah, Noor Athira; JOPRI, MOHD HATTA; Shair, Ezreen Farina (World Academic Publishing, 2013)
Bilinear time-frequency distributions (TFDs) are developed to represent time-varying signal jointly in time frequency representation (TFR). The TFDs offer a good time and frequency resolution, are appropriate to analyze power quality signals that consist of magnitude variation and multiple frequencies. However, the TFD suffers from cross-terms interferences because of their bilinear structures. In this paper, smooth-windowed Wigner-Ville distribution (SWWVD) is used to analyze power quality signals. The power quality signals are swell, sag, interruption, harmonic, interharmonic and transient. To get an accurate TFR, the parameters of the separable kernel are estimated from the signal. A set of performance measures are defined and used to compare the TFR for various kernel parameters.